1998
DOI: 10.1210/endo.139.12.6378
|View full text |Cite
|
Sign up to set email alerts
|

Biological Response to ErbB Ligands in Nontransformed Cell Lines Correlates with a Specific Pattern of Receptor Expression

Abstract: The human epidermal growth factor receptor (HER or ErbB) family consists of four distinct members, including the epidermal growth factor (EGF) receptor (EGFR, HER1, or ErbB1), ErbB2 (HER2 or neu), ErbB3 (HER3), and ErbB4 (HER4). Activation of these receptors plays an important role in the regulation of cell proliferation, differentiation, and survival in several different tissues. Binding of a specific ligand to one of the ErbB receptors triggers the formation of specific receptor homo- and heterodimers, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Prigent et al (1992) reported an immunohistochemical and Northern blot study on normal adult and fetal tissues and found that ErbB3 was expressed in the adult heart. In the late 1990s, however, a series of studies in neonatal and adult cardiac hearts concluded that ErbB4 and ErbB2 were the principal receptor and partner, respectively, of NRG‐1β in the heart (Sundaresan et al, 1998; Zhao et al, 1998; Rohrbach et al, 1999). ErbB3 was shown to be expressed during embryonic stages but to be switched off after birth (Zhao et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prigent et al (1992) reported an immunohistochemical and Northern blot study on normal adult and fetal tissues and found that ErbB3 was expressed in the adult heart. In the late 1990s, however, a series of studies in neonatal and adult cardiac hearts concluded that ErbB4 and ErbB2 were the principal receptor and partner, respectively, of NRG‐1β in the heart (Sundaresan et al, 1998; Zhao et al, 1998; Rohrbach et al, 1999). ErbB3 was shown to be expressed during embryonic stages but to be switched off after birth (Zhao et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only the expression of ErbB1, ErbB2, and ErbB4 has been documented in the adult heart (Sundaresan et al, 1998; Zhao et al, 1998; Rohrbach et al, 1999). ErbB3 is expressed during embryonic stages but not in the adult heart (Zhao et al, 1998).…”
mentioning
confidence: 99%
“…In vitro , BTC stimulates proliferation of the rat insulinoma cell line INS‐1, but not of the less differentiated line, RINm5F (Huotari et al, 1998). BTC also promotes proliferation of a fetal rat pancreatic epithelial cell line, BUD (Sundaresan et al, 1998). EGF itself increases proliferation of mesenchyme‐free rat pancreatic epithelium at embryonic day (E) 13, while preventing endocrine cell differentiation (Cras‐Meneur et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Real‐time PCR has been described in detail by other investigators (23–26). This technique uses an oligonucleotide hybridization probe that is labeled with a reporter fluorescent dye (6‐carboxy‐fluorescein) at the 5′ end and with a quencher fluorescent dye (6‐carboxy‐tetramethylrhodamine) at the 3′ end.…”
Section: Methodsmentioning
confidence: 99%